A pre-processing tool for Web usage mining in the distance education domain - Marquardt, C.G.; Becker, K.; Ruiz, D.D. (Proceedings. International Database Engineering and Applications Symposium, 2004. IDEAS '04, 2004)
Web usage mining (WUM) is the process of extracting navigation behaviour patterns that allow analysing users' interactions with Web-based environments. We discuss the impact of developing the WUM preprocessing phase according to concepts, problems and goals specific to Web-based learning environments. We present a tool prototype that automates typical tasks performed in the pre-processing phase, by offering operators that implement these tasks. The tool seeks for the active involvement of domain-related people (e.g. instructors). Functionality makes easier the alignment of mining goals with required pre-processing tasks, by addressing the configuration of operators visually and by enabling the reuse of existing configurations.